Electrocatalytic Study at Silver/Polypyrrole Nanowires Composite Modified Electrodes - LING ZHANG*, XIU; XIN XING†, JIAN; JIN‡, FENG (Asian Journal of Chemistry, 2024)
Silver modified composite electrodes were prepared by electrochemical method on the polypyrrole (PPy) nanowires modified electrodes. The surface behaviour of it was investigated by scanning electronic microscopy and energy-dispersive X-ray analysis (EDX). The electrocatalytic activity of it was characterized by electroreduction of nitrate and their reduction products. The effect of solution pH, electrolytic potentials and electrolytic current density on nitrate electrolysis and the product were also examined. The experimental results indicate that Ag/ PPy nanowires composite modified electrodes have higher catalytic activity toward nitrate reduction, the nitrite and ammonia in the resulted solution products are always at low concentration. This result shows that the electrodes have promising application in environmental remediation.